CHEMICAL COMPOSITION OF THE PURPLE CONEFLOWER (ECHINACEA PURPUREA) PLANT - Asqarov Ibrohim Rakhmonovich; Mo‘minjonov Mirjalol Muqimjon ogli; Mo‘minjonova Mukarramkhon Sherzodbek qizi (Modern American Journals, 2025)
The Purple Coneflower (Echinacea purpurea) is a medicinal plant widely recognised for its immunostimulatory and therapeutic properties. This study aimed to investigate the chemical composition of Echinacea purpurea through qualitative and quantitative analyses. The plant samples were collected during the flowering stage and subjected to drying, extraction, and subsequent laboratory analysis. Advanced chromatographic (HPLC) and spectroscopic methods were employed to identify major classes of bioactive compounds, including phenolic acids, flavonoids, and essential oils.
Keywords: Echinacea purpurea, root, leaf, flower, stem, moisture, ash content, chemical composition, chemical elements, proteins, amino acids, polyphenols.